The Risk of Osseointegration in the Coronavirus Disease 19 Pandemic - Mulinari-Santos, Gabriel (2021)
ABSTRACT: Coronavirus disease 19 (COVID-19) is associated with respiratory complications but also with alterations on bone metabolism. Coronavirus disease 19, therefore, might be a risk factor for osseointegration. Recent studies suggest that severe acute respiratory syndrome coronavirus 2 is related with bone abnormalities mainly for act via renin-angiotensin system. This report aims to list the bone alterations caused by coronavirus disease 19 and the possible consequences on the peri-implant bone healing. The current data add to the accumulating knowledge that coronavirus disease 19 may negatively impact the osseointegration and it requires further research.